Temporal effect on cell stage and location of embryos in goats treated with gonadotropins - Goel, A K; Agrawal, K P (The Indian Journal of Animal Sciences, 2012)
PMSG (750-1000 IU) or FSH (10-15 mg in tapering doses. 4-day schedule) or combination (12 mg FSH and 750 IU PMSG) were used to induce superovulation in 49 cyclic parous indigenous goats. Oestrus was regulated by progestogens/ luteolytic agents or their combination, hCG @500 IU was used as ovulating hormone. Does were laparotomized at 60-120 hr post onset of oestrus. Fallopian tubes (FT) and uterine horns (UH) were flushed separately. Overall recovery rate was 61.23%; 148 (51.22%) out of 289 recovered embryos were fertilized and transferable. FSH (equine) had an adverse effect on embryo quality (71.96% uncleaved eggs) without affecting ovulation rate. There was no remarkable difference in location and quality (cell stage) of recovered embryos in remaining groups. Majority of embryos recovered (FT) at 60-72 hr post onset of oestrus were 2-8 cell stages and trend continued lip to 96 hr with the addition of a few 12-cell stages at fourth day of collection. No embryo of 16-cell stage was recovered during this period. A few embryos of 12-cell stages were also recovered from uterine flushings.